1999
DOI: 10.1055/s-1999-122
|View full text |Cite
|
Sign up to set email alerts
|

Occult Dysplasia is Disclosed by Lugol Chromoendoscopy in Alcoholics at High Risk for Squamous Cell Carcinoma of the Esophagus

Abstract: We concluded that individuals who abuse alcohol, smoke and consume 'maté' have a high prevalence of dysplastic lesions that can be better detected by LCE. Esophagi with unstained areas had an eight-fold higher chance of revealing dysplasia than the uniformly stained ones. LCE is an easy and inexpensive method. It improves the detection of dysplasia and should be added to conventional upper GI endoscopy in patients at risk for SCCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 13 publications
3
48
0
6
Order By: Relevance
“…This high percentage compares well or even surmounts the rates observed in previous studies (Makuuchi et al, 1996;Meyer et al, 1997;Fagundes et al, 1999;Tincani et al, 2000;Petit et al, 2001) and provides strong evidence for the efficacy of the screening protocol used in this study. Various alternative screening strategies have been described.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This high percentage compares well or even surmounts the rates observed in previous studies (Makuuchi et al, 1996;Meyer et al, 1997;Fagundes et al, 1999;Tincani et al, 2000;Petit et al, 2001) and provides strong evidence for the efficacy of the screening protocol used in this study. Various alternative screening strategies have been described.…”
Section: Discussionsupporting
confidence: 89%
“…In order to detect early lesions even in a macroscopically normal looking and staining oesophagus (Fagundes et al, 1999), we took multiple biopsies according to a systematic endoscopic biopsy protocol and found that 6.8% (10 out of 148) of the patients biopsied had oesophageal squamous cell dysplasias (synonym: intraepithelial neoplasias; Gabbert et al, 2000;Schlemper et al, 2000a -c). This high percentage compares well or even surmounts the rates observed in previous studies (Makuuchi et al, 1996;Meyer et al, 1997;Fagundes et al, 1999;Tincani et al, 2000;Petit et al, 2001) and provides strong evidence for the efficacy of the screening protocol used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, patients were selected with esophageal symptoms and 86 (10.6%) patients were observed to have dysplasia/early carcinoma, among whom 19 (2.3%, 19/812) cases had severe dysplasia/early carcinoma. The detection rate of severe dysplasia/early carcinoma almost reached that of the high-risk population (13)(14)(15)(16)(17). In this study, these patients were divided into three groups according to symptoms, and 8.3% patients who had reflux, 17.2% patients who had dysphagia, and 15.8% patients who had globus sensation, were also observed to have dysplasia/early ESCC.…”
Section: A B Cmentioning
confidence: 79%